Zákaznicky orientovaný marketing stavebního podniku - Slováček, Štěpán (Vysoké učení technické v Brně. Fakulta stavební)
Tato bakalářská práce se zabývá problematikou marketingové komunikace stavební společnosti se zaměřením na tvorbu a chápání goodwill. Teoretická část práce popisuje základní pojmy z oblasti trhu, marketingu, goodwill a procesu získávání informací. V praktické části je zhodnocen současný stav stavebního trhu se zohledněním marketingových strategií a s nimi spjatou tvorbu a udržování goodwill. Následně jsou předloženy návrhy postupů pro posílení goodwill zkoumaných společností.

This bachelor thesis deals with the issue of marketing communication of a construction company with a focus on the creation and understanding of goodwill. The theoretical part describes the basic concepts of market, marketing, goodwill and information retrieval process. The practical part evaluates the current state of the construction market, taking into account the marketing strategies and the related creation and maintenance of goodwill. Subsequently, proposals for procedures for strengthening the goodwill of the companies under review are presented.
Customer-oriented marketing of a construction company
Keywords: Marketing; goodwill; marketingový průzkum; marketingová komunikace; Marketing; goodwill; marketing research; marketing communication